Induction of Inhibitory Receptors on T Cells During Plasmodium vivax Malaria Impairs Cytokine Production - Costa, Pedro A. C. (J Infect Dis, 2015)
The function and regulation of the immune response triggered during malaria is complex and poorly understood, and there is a particular paucity of studies conducted in humans infected with Plasmodium vivax. While it has been proposed that T-cell-effector responses are crucial for protection against blood-stage malaria in mice, the mechanisms behind this in humans remain poorly understood. Experimental models of malaria have shown that the regulatory molecules, cytotoxic T-lymphocyte attenuator-4 (CTLA-4), lymphocyte activation gene-3 (LAG-3), and programmed death-1 (PD-1) are involved in the functional impairment of T cells during infection. Our goal was to define the role of these molecules during P. vivax malaria. We demonstrate that infection triggers the expression of regulatory molecules on T cells. The pattern of expression differs in CD4(+) and CD8(+) T cells. Higher frequencies of CD4(+) express more than 1 regulatory molecule compared to CD8(+) T cells. Moreover, lower proportions of CD4(+) T cells coexpress regulatory molecules, but are still able to proliferate. Importantly, simultaneously blockade of the CLTA-4, PD-1, and T-cell immunoglobulin and mucin–3 signaling restores the cytokine production by antigen-specific cells. These data support the hypothesis that upregulation of inhibitory receptors on T cells during P. vivax malaria impairs parasite-specific T-cell effector function.